Environment : the science behind the stories - Withgott, Jay; Laposata, Matthew (USA PEARSON, 2005)
"Environment: The Science Behind the Stories 7e is written for an introductory environmental science course for non-science majors. The "central case studies" hook students with stories at the beginning of a chapter and are threaded throughout. Related "Science Behind the Stories" boxes are integrated throughout to guide students through scientific discoveries, the ongoing pursuit of questions, and an understanding of the process of science. Unfolding stories about real people and places make environmental science memorable to non-science majors, and engage them in the content"--
Includes bibliographical references and index.
Keywords: Environmental sciences